Treatment of bone loss in proximal femurs of postmenopausal osteoporotic women with AGN1 local osteo-enhancement procedure (LOEP) increases hip bone mineral density and hip strength: a long-term prospective cohort study - Howe, J. G.; Hill, R. S.; Stroncek, J. D.; Shaul, J. L.; Fayell, D.; Cheng, R. R.; Engelke, Klaus; Genant, H. K.; Lee, D. C.; Keaveny, T. M.; Bouxsein, M. L.; Huber, B. (Osteoporosis international, 2019)
This first-in-human study of AGN1 LOEP demonstrated that this minimally-invasive treatment durably increased aBMD in femurs of osteoporotic postmenopausal women. AGN1 resorption was coupled with new bone formation by 12 weeks and that new bone was maintained for at least 5-7 years resulting in substantially increased FEA-estimated femoral strength. Introduction This first-in-human study evaluated feasibility, safety, and in vivo response to treating proximal femurs of postmenopausal osteoporotic women with a minimally-invasive local osteo-enhancement procedure (LOEP) to inject a resorbable triphasic osteoconductive implant material (AGN1). Methods This prospective cohort study enrolled 12 postmenopausal osteoporotic (femoral neck T-score <= - 2.5) women aged 56 to 89 years. AGN1 LOEP was performed on left femurs; right femurs were untreated controls. Subjects were followed-up for 5-7 years. Outcomes included adverse events, proximal femur areal bone mineral density (aBMD), AGN1 resorption, and replacement with bone by X-ray and CT, and finite element analysis (FEA) estimated hip strength. Results Baseline treated and control femoral neck aBMD was equivalent. Treated femoral neck aBMD increased by 68 +/- 22%, 59 +/- 24%, and 58 +/- 27% over control at 12 and 24 weeks and 5-7 years, respectively (p < 0.001, all time points). Using conservative assumptions, FEA-estimated femoral strength increased by 41%, 37%, and 22% at 12 and 24 weeks and 5-7 years, respectively (p < 0.01, all time points). Qualitative analysis of X-ray and CT scans demonstrated that AGN1 resorption and replacement with bone was nearly complete by 24 weeks. By 5-7 years, AGN1 appeared to be fully resorbed and replaced with bone integrated with surrounding trabecular and cortical bone. No procedure- or device-related serious adverse events (SAEs) occurred. Conclusions Treating femurs of postmenopausal osteoporotic women with AGN1 LOEP results in a rapid, durable increase in aBMD and femoral strength. These results support the use and further clinical study of this approach in osteoporotic patients at high risk of hip fracture.
CRIS-Team WoS Importer:2019-12-13